THE DOMINANCE OF FATHER'S ROLE IN THE FILM NGERI-NGERI SEDAP - Aryati, Putri; Adiprabowo, Vani Dias (TONIL: Jurnal Kajian Sastra, Teater dan Sinema, 2023)
The purpose of this research is to identify the pattern of family communication in the film "Ngeri-ngeri Sedap". Film Ngeri-ngeri Sedap 2022 directed by Bene Dion tells the story of a family drama, telling the story of Pak Domu and Mak Domu who live with Sarma, their only daughter. The husband-and-wife couple wanted their three sons who had wandered for a long time to come home to attend a traditional event. But their three children refused because their relationship was not harmonious. This research was conducted with a type of qualitative research using the semiotic analysis model developed by John Fiske. The results of this study indicate that the communication in this film is quite problematic. This can be seen in the results of John Fiske's research on three levels of semiotics, namely the level of reality, the level of representation, and the level of ideology. The level of reality shows that the pattern of family communication implemented in this film has a paternalistic, namely a pattern where only one family member controls the family. In the case of this family, it is the father who controls the family.Keywords: Dominance, Fatherhood, Monopoly Communication Patterns, Film Ngeri-ngeri Sedap